2021
DOI: 10.3390/ijerph18168485
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Distress of COVID-19 and Depression in the General Population: Exploring the Role of Resilience, Anxiety, and Hope

Abstract: International evidence published so far shows that the COVID-19 pandemic has negatively impacted on global mental health. Specifically, there is some research suggesting that the psychological distress related to depression, anxiety and posttraumatic stress has impacted on the psychological well-being of the general population. Yet, there is limited evidence on the relational paths between COVID-19 traumatic distress and depression. Participants of this cross-sectional study were 456 adults 18 years old or old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 88 publications
4
16
0
Order By: Relevance
“…When people go through the adversity of COVID-19, resilience may work as a crucial factor in reducing the stressful experience, consequently maintaining people's mental health. In line with this, abundant research has demonstrated the indirect effect of resilience between stress and mental health outcomes such as depression and anxiety ( 7 , 25 ).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…When people go through the adversity of COVID-19, resilience may work as a crucial factor in reducing the stressful experience, consequently maintaining people's mental health. In line with this, abundant research has demonstrated the indirect effect of resilience between stress and mental health outcomes such as depression and anxiety ( 7 , 25 ).…”
Section: Introductionmentioning
confidence: 77%
“…These negative mental health outcomes may attribute to the stress induced by the COVID-19 pandemic, as some researchers indicated that COVID-19 related stress made people more vulnerable to developing mental health issues (3,4). Recent studies further confirmed an association between COVID-19 related stress and negative mental health outcomes (5)(6)(7). Besides, some researchers found that COVID-19 related mental health outcomes are not static but dynamic events that fluctuate with the number of infected cases (8).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, several studies have been performed to explore the effects of the COVID-19 pandemic on the mental health of the general population. The COVID-19 pandemic has been associated with anxiety, distress, fear of contagion, insomnia and depression [ 28 , 29 , 30 ]. Prolonged social distancing protocols, economic stress and unemployment rates can originate a mental health crisis; moreover, social isolation has a detrimental effect on health, for both living alone and feelings of loneliness are risk factors for the increase in suicidal behavior [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“… 16 A cross‐sectional study considering the relational path between COVID‐19 distress and depression in the general population, in which a large proportion of respondents were living in Ireland, suggested the traumatic distress of COVID‐19 to have a strong positive effect on depression, which was mediated by resilience, anxiety and hope. 17 …”
Section: Introductionmentioning
confidence: 99%